PENGARUH UPA TULANG, JUMLAH ULOS, PEKERJAAN, DAN PENDIDIKAN TERHADAP SINAMOT: KASUS PERKAWINAN BATAK TOBA DI MEDAN - Purba, Elvis Fresly; Lastri, Lastri (Jurnal Manajemen dan Bisnis, 2021)
The purpose of the research is to identify four factors that are consider to influence dowry (sinamot) in Batak Toba traditional marriage (traditional wedding) before the Covid-19 pandemic in Medan. The sample research is purposive sampling namely the parents of the groom as the providers of sinamot and financing their son’s traditional wedding. The sample method is non probability sampling, that is an accidental sampling with 40 families. Besides other the groom family (paranak), other sources of additional information are raja parhata because they can provide general information for the independent factors on sinamot. The factors considered in this research as independent variabales consist of upa tulang, number of ulos from the bride family (parboru) and two dummy variables that are job status and level education of the bride. The data is tabulated and then analyzed by multiple linear regression. The research show that four variables have a positive effect on the dowry. This is accordance with economic criteria show that upa tulang, number of ulos, job status of the bride and level education of the bride have positive effect on the sinamot. However based on partial test (t - test) only two variables have positive significant on the dowry namely upa tulang and job status of the bride. But based on simultaneous test (F-test) the four factors simultaneously effects on the dowry. Coefficient of determination (R2) is 0,846 and R square adjusted is 0,828 which means 4 independent variables are able to explain the variation of the dowry between 82,8 to 84,6 percent.